2021
DOI: 10.4081/jphr.2021.2333
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Pornographic Exposure and Addiction to Risky Sexual Behavior in Adolescents

Abstract: Background: The progress of information and technology contributes to the increasingly easier access to pornographic content. Adolescents as the highest Internet accessor become the most susceptible population to pornographic hazards, which has an impact on deviant sexual behavior. This study aimed to identify the relationship of exposure history and pornography addiction to risky sexual behavior in adolescents.Design and Methods: The data were collected online using a cross-sectional approach and involved 394… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 14 publications
1
23
0
8
Order By: Relevance
“…IA has a great impact on student's physical, psychological and social performance. In terms of physical health, it can lead to a range of problem behaviors, such as social problems ( 3 ), eating disorders ( 4 ), sleep disorders ( 5 , 6 ), risky sex ( 7 ), and even suicide ( 8 ). A meta-analysis confirmed that Problematic Internet Use (PIU) is a predictor of eating disorders in students ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…IA has a great impact on student's physical, psychological and social performance. In terms of physical health, it can lead to a range of problem behaviors, such as social problems ( 3 ), eating disorders ( 4 ), sleep disorders ( 5 , 6 ), risky sex ( 7 ), and even suicide ( 8 ). A meta-analysis confirmed that Problematic Internet Use (PIU) is a predictor of eating disorders in students ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of pornography may lead to male porn consumers masturbating more frequently than they would (Table 4 continued) otherwise. 28 Frequent masturbation (because of regular pornography use) could undermine male porn users' sexual performance, arousability, or partnered sexual interest by keeping these porn users in a near-continual state of relative postejaculatory refractory time (PERT), in which their arousal is suppressed. 26…”
Section: Effects Of Pornography Use On Sexual Response During Masturb...mentioning
confidence: 99%
“…Risky sexual behaviors among adolescents at their critical developmental stage continue to increase every year and become a concern. These problematic sexual attitudes and behaviors are influenced by several factors such as biological, environmental, and lifestyle risks associated with the advancement of information technology, especially in internet use, which is currently dominated by the 15-19 age group (Yunengsih & Setiawan, 2021). Due to the process of developing sexual feelings, adolescents continue to seek information and guidance about what is appropriate and expected, yet because perhaps psychologically adolescents are still immature, they face challenges in choosing positive messages and are overly influenced (Brown, 2001).…”
Section: The Effects Of Pornography On Adolescent Sexual Behaviormentioning
confidence: 99%
“…Furthermore, the frequency of internet use to access sexual material was found to be a predictor for being sexually active and the likelihood of having multiple sexual partners (Olarinmoye et al, 2014). Furthermore, another study that positively linked sexual behavior with pornography viewing resulting in serious problems in the adolescent population was a study conducted by Yunengsih and Setiawan (2021) who found a significant relationship between risky sexual behavior in students and age of first pornography exposure. times, so too the effect on cognition is shown from their obsessivecompulsive thinking about sexual content.…”
Section: The Effects Of Pornography On Adolescent Sexual Behaviormentioning
confidence: 99%
See 1 more Smart Citation